The analgesic efficacy of pre‐operative bilateral erector spinae plane (ESP) blocks in patients having ventral hernia repair. (11th February 2017) - Chin, K. J.; Adhikary, S.; Sarwani, N.; Forero, M.
Summary: Laparoscopic ventral hernia repair is an operation associated with significant postoperative pain, and regional anaesthetic techniques are of potential benefit. The erector spinae plane (ESP) block performed at the level of the T5 transverse process has recently been described for thoracic surgery, and we hypothesised that performing the ESP block at a lower vertebral level would provide effective abdominal analgesia. We performed pre‐operative bilateral ESP blocks with 20–30 ml ropivacaine 0.5% at the level of the T7 transverse process in four patients undergoing laparoscopic ventral hernia repair. Median (range) 24‐h opioid consumption was 18.7 mg (0.0–43.0 mg) oral morphine. The highest and lowest median (range) pain scores in the first 24 h were 3.5 (3.0–5.0) and 2.5 (0.0–3.0) on an 11‐point numerical rating scale. We also performed the block in a fresh cadaver and assessed the extent of injectate spread using computerised tomography. There was radiographic evidence of spread extending cranially to the upper thoracic levels and caudally as far as the L2–L3 transverse processes. We conclude that the ESP block is a promising regional anaesthetic technique for laparoscopic ventral hernia repair and other abdominal surgery when performed at the level of the T7 transverse process. Its advantages are the ability to block both supra‐umbilical and infra‐umbilical dermatomes with a single‐level injection and its relative simplicity.